2017
DOI: 10.4149/bll_2017_086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leptin and resveratrol on JAK/STAT pathways and Sirt-1 gene expression in the renal tissue of ischemia/reperfusion induced rats

Abstract: OBJECTIVE: Our study aimed to investigate the possible modifying effects of leptin and combined use of resveratrol on rat renal I/R injury and their relationship on signal pathways and apoptosis-related mechanisms. BACKGROUND: Renal ischemia-reperfusion (I/R) injury is an important cause of acute renal failure. METHODS: Male Sprague Dawley rats were divided into 5 groups: Control, I/R, I/R+leptin, I/R+resveratrol and I/R+leptin+resveratrol. Leptin (10 μg/kg BW) was administered (i.p.) 30 min prior to I/R. Resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…Furthermore, previous studies have demonstrated a role of leptin on regulating the JAK/STAT signaling pathway. 17,18 Therefore, together with our data, the function of leptin on the pulmonary inflammation may be partly through activating the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, previous studies have demonstrated a role of leptin on regulating the JAK/STAT signaling pathway. 17,18 Therefore, together with our data, the function of leptin on the pulmonary inflammation may be partly through activating the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, a few researches have demonstrated that leptin positively increased the STAT3 activation in inflammatory diseases including chronic inflammatory lung diseases. 17,18 Therefore, this study was designed to detect the expression levels of leptin, adiponectin, STAT3 and STAT6 mRNA and proteins in lungs and bronchoalveolar lavage fluid (BALF) as well as the activations of STAT3 and STAT6 protein in the lung tissues and evaluate the differences between the mRNA and protein expressions in obese and lean mice in experimental asthmatic model.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of TNF-α and liver cell membrane TNF-α receptor 1 (TNF-αR1) can induce intracellular double-stranded DNA to fragment, thereby resulting in stem cell apoptosis. In addition, TNF-α triggers inflammatory responses by activating NF-κB, which exacerbates liver injury [ 37 ]. IFN-γ is a proinflammatory cytokine that increases the sensitivity of hepatocytes to TNF-α, rendering hepatocytes to further damage [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT pathway play roles in acute kidney injury, 4,23 and studies indicated that JAK/STAT pathway is associated with the MSC-mediated tissue repair. 15 Herein we hypothesize that engineering MSCs with overexpressed HO-1 can improve treatment efficacy for AKI.…”
Section: Introductionmentioning
confidence: 99%